1983
DOI: 10.1002/jez.1402280116
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of laminin within the mouse ovary

Abstract: Laminin, a noncollagenous glycoprotein, was observed in the mouse ovary using a direct immunofluorescence technique. Laminin was localized within the basal lamina underlying growing and atretic ovarian follicles, blood vessels, and the germinal epithelium. In addition, laminin was also present at the periphery of individual corpora lutea cells. The presence of laminin in the basal lamina underlying ovarian follicles may be important for the passage of material between the follicle cells and the connective tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
2
9
0
1
Order By: Relevance
“…By immunohistochemistry using antibodies raised against LN-1, we have confirmed the presence of LN in basement membrane, granulosa and theca cells of ovine antral follicles, as shown previously in various animal species (Bagavandoss et al 1983, Wordinger et al 1983, Bortolussi et al 1989, Leardkamolkarn & Abrahamson 1992, Zhao & Luck 1995, Lee et al 1996, Huet et al 1997, van Wezel et al 1998, Alexopoulos et al 2000. Laminins are heterotrimeric proteins containing , and subunits, and the association of structural isoforms of these subunits gives rise to different LN (Mercurio 1995).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…By immunohistochemistry using antibodies raised against LN-1, we have confirmed the presence of LN in basement membrane, granulosa and theca cells of ovine antral follicles, as shown previously in various animal species (Bagavandoss et al 1983, Wordinger et al 1983, Bortolussi et al 1989, Leardkamolkarn & Abrahamson 1992, Zhao & Luck 1995, Lee et al 1996, Huet et al 1997, van Wezel et al 1998, Alexopoulos et al 2000. Laminins are heterotrimeric proteins containing , and subunits, and the association of structural isoforms of these subunits gives rise to different LN (Mercurio 1995).…”
Section: Discussionsupporting
confidence: 85%
“…This basement membrane is believed to play a role in influencing proliferation and differentiation of GC (Amsterdam et al 1989, Luck 1994 and in protecting them from entering apoptosis in early atretic follicles (Monniaux et al 1999). Laminin (LN) has previously been shown to be one of the most abundant ECM components within the basement membrane (Wordinger et al 1983, Leardkamolkarn & Abrahamson 1992, Zhao & Luck 1995, Lee et al 1996, Huet et al 1997, van Wezel et al 1998, Alexopoulos et al 2000. In vitro, purified LN used as a culture substratum improves GC survival in rat (Aharoni et al 1996) and sheep (Huet et al 2001) and stimulates their proliferation in sheep (Huet et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen type IV, laminin, and heparan sulfate proteoglycans are present in the basement membrane of the rodent ovarian follicles [19][20][21]. Interestingly, immunoelectron microscopic studies of rat ovaries have shown that laminin is absent from the primordial follicles but is detected in the preantral and antral follicles [22].…”
Section: Discussionmentioning
confidence: 94%
“…Unfortunately, the composition, synthesis, regulation, and function of the follicular basal lamina that surrounds the membrana granulosa from primordial to preovulatory stages are poorly understood. Type IV collagen, fibronectin, and laminin have been immunolocalized to the follicular basal lamina [44][45][46][47], and our recent evidence suggests that bovine granulosa cells synthesize at least the structural components of the follicular basal lamina [31,32]. Although some components of the basal lamina in some organs are secreted by the stroma [48,49], in most cases the structural components are secreted by epithelial cells (see [50]).…”
Section: Figmentioning
confidence: 99%